APPLICATION OF SIMULATION MODELS FOR PROGRAMMING OF ROBOTS - Jakubiec, Beata (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
In recent years, there has been an increasing robotization of many areas of life. This requires knowledge of issues related to robots and their programming. Devices of this type, especially large industrial or medical robots, are very expensive, or they may be hardly affordable for educational purposes. Simulation models are helpful in such situation. The aim of the article is to present the possibilities of using simulation models of robots and robotic stations in the educational and research process. Specialized software packages make it easier not only to understand how robots work, but they also allow to test different operating conditions of the designed computer model of the real robotized process.